Construction of a Selectable Marker Recycling System and the Use in Epitope Tagging of Multiple Nuclear Genes in the Unicellular Red Alga Cyanidioschyzon merolae. (7th August 2018) - Takemura, Tokiaki; Imamura, Sousuke; Kobayashi, Yuki; Tanaka, Kan
Abstract: The nuclear genome of the unicellular red alga Cyanidioschyzon merolae can be modified by homologous recombination with exogenously introduced DNA. However, it is presently difficult to modify multiple chromosome loci because of the limited number of available positive selectable markers. In this study, we constructed a modified URA5.3 gene ( URA5.3T ), which can be repeatedly used for nuclear genome transformation, as well as two plasmid vectors for 3 FLAG- or 3 Myc-epitope tagging of nuclear-encoded proteins using URA5.3T . In the URA5.3T marker, the promoter region and open reading frame were located between directly repeated URA5.3 terminator sequences, and the URA5.3 gene can be eliminated by 5-fluoroorotic acid selection through homologous recombination. To demonstrate the utility of the constructed system, a 3 FLAG-tag and 3 Myc-tag were introduced at the C-termini of two of the six Rab proteins in C. merolae, CmRab18 and CmRab7, respectively, and the differential expression levels were successfully monitored by immunoblot analysis using these epitope tags. The URA5.3T marker's introduction and elimination cycle can be repeated. Thus, we have constructed a marker recycling system for C. merolae nuclear transformation. A novel procedure to obtain a high plating efficiency of C. merolae cells on solid gellan gum plates is also presented.